Liver transplantation for neotropical polycystic echinococcosis caused by Echinococcus vogeli: a case report - Genzini,Tércio (2013)
Neotropical polycystic echinococcosis (NPE) is a parasitic disease caused by cestodes of Echinococcus vogeli. This parasite grows most commonly in the liver, where it produces multiples cysts that cause hepatic and vessel necrosis, infects the biliary ducts, and disseminates into the peritoneal cavity, spreading to other abdominal and thoracic organs. In cases of disseminated disease in the liver and involvement of biliary ducts or portal system, liver transplantation may be a favorable option. We present a report of the first case of liver transplantation for the treatment of advanced liver NPE caused by E. vogeli.